NOVEL APP FOR SMARTPHONES AND TABLETS TO OPTIMIZE AND STANDARDIZE DRUG PRESCRIPTIONS IN NEONATES. Issue 1 (14th December 2015) - Rodieux, Frederique; Sanduja, Sachin; Pfister, Marc; Anker, John Van den
Abstract : Background: Neonates in intensive care units (NICU) are highly vulnerable to medication errors. Studies indicate that junior doctors have a prescribing error rate of up to 10%. Prescription errors result in overdosing or underdosing and affect clinical outcomes. Advances in mobile technology have brought opportunities for creating bedside decision support tools, including smartphone applications (apps). Ownership of smartphones and tablets by medical professionals is 80% or higher. The most commonly used apps amongst medical trainees are drug prescription guidelines and calculators. Results: Novel drug prescription app based on reference texts such as the British National Formulary for children (BNFc), neonatal formulary seventh edition (NNF7) and the Red Book of the American Academy of Pediatrics. This app permits neonatologists to easily access up-to-date dose information and quickly calculate individual dose based on a patient's characteristics (e.g. weight, age, serum creatinine value). Conclusion: Apps for smartphones and tablets can serve as bedside decision support tools in neonatology. Pharmacometric modeling can be built in such apps to leverage historical and current patient data, individualize dosing strategies, and further optimize treatment benefits for neonates. Furthermore such applications may facilitate standardization of drug prescriptions among the nine NICUs in Switzerland.